Implementation of Electronic KTP (E-KTP) Services in the Era of New Habit Adaptation (AKB) of the Population and Civil Registration Service (DINDUKCAPIL) of Pekalongan City, Central Java - Maya Sofiana; Endang Supriyadi; Rita Wahyuni (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Population administration services are one of the government's general duties in terms of public services. The activities of managing and controlling data and publishing population documents are part of population administration. In this case the Electronic Identity Card (E-KTP) is the legal identity of the resident in which individual data is contained. However, in its application in the field, the E-KTP service still has obstacles so that it is not maximally felt by the people. As for the obstacles found in E-KTP services, among others, in terms of personnel, namely the lack of optimal service provided can be from the aspect of behavior caused by time limit or work pressures so that it affects the quality of service besides that in terms of lack of infrastructure or disruption of equipment such as server connections and limited blanks, and lack of clear information for the general public. The government's latest policy is rolling so that the people can tolerate with Covid-19. Based on recommendations of the World Health Organizations (WHO), the recommendation of a New Normal is not only trending around the world. then the recommendation in Indonesia changed to